City : a guidebook for the urban age - Smith, Peter D. (Peter Daniel), 1965- (Bloomsbury, 2012)
Acclaimed author and independent scholar P. D. Smith explores what it was like to live in the first cities, how they have evolved, and why in the future, cities will play an even greater role in human life.